Translation Practices and the Issue of Directionality in China - Wang, Baorong (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2011)
Directionality is one of the most interesting recent developments in translation studies in the West. The scene, however, is rather different in China with a long history of inverse translation. This article aims to outline translation practices in China and Chinese thinking on directionality while providing a few pointers for further research. Part one surveys major translation projects that were carried out or are being carried out and how Chinese translation scholars thought/think about directionality. The survey covers nineteen centuries from the 2nd century A.D. through the present time, albeit most of the data are devoted to the periods from the turn of the 20th century. It is found that although inverse translation is an age-old practice in China, the issue of directionality began to be seriously considered and debated only in the early 1980s, and that there has been increased attention to the topic in recent years. Part two briefly reviews the current status of research and concludes that directionality is an under-researched area in Chinese translation studies. The article ends with some suggestions for further research on the subject in the Chinese context, drawing on the latest research conducted in the West.